Implementation of School-Based Mental Health Programs in Promoting Resilience among Adolescents of Bato, Catanduanes - Toledana, John Eric; Emerenciana, Anthony T.; Barra, Regina Salve B.; Taule, Ma. Monette S.; Torno, John Vincent A. (Alta Dharma Publisher, 2025)
Background: Mental health issues among adolescents are a growing concern. The implementation of school-based mental health programs plays a crucial role in promoting resilience and emotional stability. However, the extent of their effectiveness in specific contexts, such as in Bato, Catanduanes, remains underexplored. Objective: This study aims to assess the effectiveness of a school-based mental health program in promoting resilience and well-being among adolescents in Bato, Catanduanes. It evaluates the level of implementation, identifies challenges, and examines strategies used to support students' mental health. Method: The study employed a quantitative-descriptive research design. Data were gathered through surveys administered to students, teachers, and school administrators. Mean scores were used to determine the extent of program implementation, and statistical analysis was conducted to evaluate its effectiveness. Result: Findings revealed that while mental health programs were moderately implemented in schools, certain areas, such as access to mental health resources and collaboration with mental health professionals, were lacking. Key strategies such as counseling sessions, mental health awareness campaigns, and stress management workshops were found to be effective in supporting students’ well-being. However, challenges such as limited resources, lack of trained personnel, and inconsistent parental involvement hindered the program’s full potential. Conclusion: The study highlights the need for strengthening school-based mental health initiatives through better resource allocation, enhanced training for educators, and increased community and parental involvement. Recommendation: It is recommended that schools implement more structured mental health programs, increase collaboration with mental health professionals, and provide training for teachers to effectively address students’ psychological needs. Strengthening parental involvement and ensuring adequate funding for mental health resources are also essential to enhance the program's impact.